1971
DOI: 10.1002/hlca.19710540523
|View full text |Cite
|
Sign up to set email alerts
|

The Competition between Spin Orbit Coupling and Conjugation in Alkyl Halides and its Repercussion on their Photoelectron Spectra

Abstract: Szwnmary.A crude molecular orbital model for alkyl halides is proposed, which provides a semi-quantitative rationalization for the following experimental observations : (a) In the photoelectron spectra of alkyl halides R X (symmetry C,) the lone pair band is split into two components, separated by a gap A . This gap is equal to the splitting associated with spin-orbit coupling in systems where X lies on a symmetry axis of order n > 3. (b) The vibrational pattern of the two components indicates substantial conj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
0
3

Year Published

1973
1973
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(30 citation statements)
references
References 17 publications
6
21
0
3
Order By: Relevance
“…The atomic spin-orbit coupling parameters are 0.073 and 0.305 eV for Cl and Br, respectively [57], thus it might be anticipated that the splitting between the essentially Br lone-pair orbitals in CHFClBr would be greater than that between the essentially Cl lone-pair orbitals, as is commonly observed in halogen containing molecules [20,21,23,24,26].…”
Section: Resultsmentioning
confidence: 97%
“…The atomic spin-orbit coupling parameters are 0.073 and 0.305 eV for Cl and Br, respectively [57], thus it might be anticipated that the splitting between the essentially Br lone-pair orbitals in CHFClBr would be greater than that between the essentially Cl lone-pair orbitals, as is commonly observed in halogen containing molecules [20,21,23,24,26].…”
Section: Resultsmentioning
confidence: 97%
“…It has been demonstrated that this magnitude of splitting also occurs in alkyl bromides of C, symmetry and is insensitive to the degree of conjugation of n;, with other a" orbitals (19). This behaviour has been explained with the use of a simple orbital model which showed that two opposing trends, increased splitting with increased conjugation of n;, and increased spin-orbit splitting with increased localization on the halogen atom, compensated each other (20). A similar situation is believed to hold in the case of propenoyl bromide.…”
Section: Propenoyl Chloridementioning
confidence: 96%
“…9: 10,1 eV; vgl. [27]) nicht überlappt. Eine Optim ie rung der Reaktionsbedingungen mit Hilfe PE-spektroskopischer Echtzeit-Gasanalytik [12] könnte zu sätzlich anhand der Spin/Bahn-gekoppelten HBr-Ionisierungsnadeln bei 11,70 eV und 12,03 eV [16] Die zum Vergleich zusätzlich untersuchte Thermolyse von Bromcyclobutan im leeren Q uarzrohr bei IO-2 mbar zeigt bei etwa 770 K Ringöffnung zu 4-Brombuten-1 und oberhalb 800 K beginnende H Br-A bspaltung zu Butadien (vgl.…”
Section: Bromcy Clobutanunclassified